Grand Analysis of Government Strategic Policy Design in Field of Education in the Era of Industrial Revolution 4.0 - Fadhilah, Fadhilah; Nailufar, Fanny; Ellianti, Ellianti; Saputra, Nanda; Herman, Herman (Journal of Posthumanism, 2025)
This study aims to determine the grand design of government strategy policies in the field of education in the era of Industrial Revolution 4.0. The method used in this study was qualitative descriptive. The qualitative descriptive approach aims to describe social phenomena with a focus on solving relevant problems, both in the present and future. Qualitative descriptive research aims to describe existing phenomena in both natural and human-engineering. Data collection techniques generally consist of four main methods: observation, interviews, documentation, triangulation or a combination of various methods. The results of this study showed that the world, especially Indonesia, is currently entering a new industrial era marked by digitalization in various sectors of life. Experts call this phase the Industrial Revolution 4.0. The rapid development of digital technology is expected to facilitate and increase human productivity, effectiveness, and efficiency in performing daily activities. The industrial revolution can be understood as a major change that occurs quickly, fundamentally, and radically, affecting the way humans live. The industrial revolution 4.0 is predicted to bring various changes, both positive and negative, to humanity. Thus, Indonesia needs to anticipate early on. The Indonesian government has prepared plans and strategies to enter the digital era through the Making Indonesia 4.0. To support this initiative, reliable human resources (HR) that are ready to face challenges are needed. Therefore, the government has formulated a strategic policy in the field of education. One of these policies is the 2013 Curriculum (K13) and strengthening character education (PPK), which is designed to prepare the next generation to face Industrial Revolution 4.0.